2021
DOI: 10.1177/1098612x211036795
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in British Shorthair cats in Sweden

Abstract: Objectives The primary objective of this study was to investigate the prevalence of epileptic seizures and of presumed idiopathic epilepsy (PIE, describing epilepsy of unknown origin) in a cohort of British Shorthair (BSH) cats in Sweden. The secondary objective was to describe epileptic seizure characteristics and outcome for cats with PIE. Methods Owners of BSH cats born between 2006 and 2016 and registered with SVERAK (the Swedish Cat Clubs’ National Association) were invited to reply to a questionnaire abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Cluster seizures are defined as ≥2 or more seizures within a 24‐hour period 10 . They are common in veterinary medicine with reported incidence of 38% to 77% in dogs and 27% to 43% in cats 11‐14 . Cluster seizures may evolve into status epilepticus with 1 study showing convulsive status epilepticus in 44% of human patients with cluster seizures 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster seizures are defined as ≥2 or more seizures within a 24‐hour period 10 . They are common in veterinary medicine with reported incidence of 38% to 77% in dogs and 27% to 43% in cats 11‐14 . Cluster seizures may evolve into status epilepticus with 1 study showing convulsive status epilepticus in 44% of human patients with cluster seizures 15 .…”
Section: Introductionmentioning
confidence: 99%
“… 10 They are common in veterinary medicine with reported incidence of 38% to 77% in dogs and 27% to 43% in cats. 11 , 12 , 13 , 14 Cluster seizures may evolve into status epilepticus with 1 study showing convulsive status epilepticus in 44% of human patients with cluster seizures. 15 This study showed that patients who experience cluster seizures are at a significantly higher risk for convulsive status epilepticus than are patients with nonclustered seizures.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Although the terminology for epilepsy classification has been agreed on in dogs, 3 no consensus has been reached for cats. 2 , 4 8 Therefore, this paper will use ‘presumptive idiopathic epilepsy’ (PIE) when referring to idiopathic epilepsy in cats. The prevalence of PIE in cats with recurrent epileptic seizures has been reported to be in the range of 22%–75%, 1 , 2 , 7 , 9 12 with the majority having seizure onset at 1–5 years.…”
Section: Introductionmentioning
confidence: 99%